The snow day from the Black Lagoon - Thaler, Mike, 1936-2024; Lee, Jared (Minneapolis, MN : Spotlight, a division of the ABDO Group, 2014)
After getting so bundled up that he can hardly move, Hubie tries to enjoy his snow day off from school.
3.7.
3-6
700
Accelerated Reader AR
Keywords: Snow -- Fiction